Análise experimental do arrasto em colunas de perfuração parcialmente imersas em leito de cascalhos - Peliano, Saul Vieira (2018)
The present work evaluated experimentally the drag’s force on a drill string, while it’s pulling out of horizontal well partially filled with cuttings bed. For accomplish this task, it was constructed an experimental unit that reproduces a horizontal well and its essential characteristics. Furthermore, the apparatus allows axial movement of the column into the well and the monitoring of the force of traction applied in the drill string. Thus, it was evaluated the sensibility of the drag force to the variation of three parameters intrinsic to the problem: the cuttings bed’s height; the cross-sectional area of the bit; and, the columns translation velocity. The results indicated that the elevation of cuttings bed’s height causes the increase of the drag due to two factors: the elevation of the contact area between the column and the cuttings bed; and, the increase of cuttings plug’s length. The combination of these factors represented a maximum increase of 267% in drag’s force for an 80% elevation in cuttings bed’s height. The enlargement of bit’s crosssectional area represented as well the increase of drag due to the augmentation of plug’s length and, in some cases, resulted in the stuck column. Lastly, the increase of drill string’s velocity represented a reduction of cuttings plug’s length for all cases studied, which meant a reduction of 53% of drag. However, in some tests the reduction of cuttings bed’s length did not mean decrease of drag.